Negative pressure therapy for the treatment of complex wounds - RENAN VICTOR KÜMPEL SCHMIDT LIMA; PEDRO SOLER COLTRO; JAYME ADRIANO FARINA JÚNIOR (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT The objective of this study is to evaluate the effectiveness of negative pressure therapy (NPT) in the treatment of complex wounds, with emphasis on its mechanisms of action and main therapeutic indications. We searched the Pubmed / Medline database for articles published from 1997 to 2016, and selected the most relevant ones. The mechanisms of action of NPT involveboth physical effects, such as increased perfusion, control of edema and exudate, reduction of wound dimensions and bacterial clearance, and biological ones, such as the stimulation of granulation tissue formation, microdeformations and reduction of Inflammatory response. The main indications of NPT are complex wounds, such as pressure ulcers, traumatic wounds, operative wound dehiscences, burns, necrotizing wounds, venous ulcers, diabetic wounds, skin grafts, open abdomen, prevention of complications in closed incisions and in the association with instillation of solutions in infected wounds.